Dinamika Intrapreneurship di Perusahaan Denim Earthy Genova: Suatu Pendekatan Kualitatif - Salsabila, Nardina; Purnomo, Margo; Purbasari, Ratih (Bahtera Inovasi, 2024)
This study examines the dynamics of intrapreneurship at Earthy Genova, a denim company that relies on both online and offline sales. Intrapreneurship, which involves innovation and employee initiative, plays a critical role in developing more creative and responsive marketing strategies to adapt to market changes. This research uses a qualitative method with an in-depth case study design, where data is collected through observation and semi-structured interviews with the company's owner. The findings reveal that intrapreneurial experiences at Earthy Genova have improved product and service quality, strengthened customer loyalty, and enhanced the company’s competitiveness in the denim industry. Innovations, such as the development of premium denim products and a customer-oriented approach, have significantly contributed to the company's success. The study concludes that intrapreneurship is a key factor in Earthy Genova's ability to navigate the challenges of the dynamic fashion industry. This research provides important insights for other e-commerce businesses regarding the importance of innovation and managerial capabilities in maintaining customer loyalty.